2000
DOI: 10.1007/pl00000720
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinins in regulation of gastric motility and secretion

Abstract: The tachykinins constitute a family of neu-receptors are generally present on the musculature, NK-1 receptors on both neurons and muscles, and NK-3 ropeptides with a common C-terminal amino acid sereceptors on neurons only. Tachykinins stimulate motilquence. The best known tachykinin is substance P. Tachykinins are found in the nerve plexuses and nerve ity in all parts of the stomach, but tachykinins also fibers in the stomach of all species examined. The circu-appear to inhibit motility in certain situations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 83 publications
(104 reference statements)
0
19
0
1
Order By: Relevance
“…24,25) Therefore substance P may not only play a role in the mediation of peristaltic contractions, but also a pathophysiologic role in the increased blood flow in the small intestine. 8) However, since there are no findings that the increase in intestinal blood flow by DKCT is related to substance P and that it participates in the physiologic regulation of mucosal blood flow in the gastrointestinal tract, further studies are needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25) Therefore substance P may not only play a role in the mediation of peristaltic contractions, but also a pathophysiologic role in the increased blood flow in the small intestine. 8) However, since there are no findings that the increase in intestinal blood flow by DKCT is related to substance P and that it participates in the physiologic regulation of mucosal blood flow in the gastrointestinal tract, further studies are needed.…”
Section: Resultsmentioning
confidence: 99%
“…6) Substance P is widely distributed in the central and peripheral nervous system and in the enteroendocrine cells of the gut 7) and it participates in the regulation of gastrointestinal motility, secretion, and blood flow. 8) Recently, it has been reported that DKCT increases intestinal blood flow, which is mainly mediated by CGRP, in rats. 9) However, the effects of DKCT on plasma CGRP and substance P levels in humans have not been described previously.…”
mentioning
confidence: 99%
“…Substance P participates in the regulation of gastrointestinal motility and secretion [14][15][16]. It also has an emetic action at the central nervous system [17].…”
Section: Discussionmentioning
confidence: 99%
“…10) Substance P is widely distributed in the central and peripheral divisions of the nervous system and in the enteroendocrine cells of gut, 11) and it participates in the regulation of gastrointestinal motility and secretion. 12) We reported that single administration of cetraxate caused significant increases in plasma CGRP and substance P levels. 13) Cetraxate is absorbed from stomach and intestine, and by esterase, rapidly metabolized to tranexamic acid and 3-(phydroxyphenyl)propionic acid in plasma (Fig.…”
Section: Introductionmentioning
confidence: 95%